Nowe zagrożenia paradygmatu administracji publicznej demokratycznego państwa prawnego - Lipowicz, Irena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Democracy, rule of law and the public administration in the balance between two powers: parliament and judiciary are the crucial points of the contemporary western civilisation. The doctrine of the administrative law and the public administration in the longstanding development performed the paradigm of the public administration, generally accepted in the countries of the European Union among them in Poland. But in the last few years we could observe the consequences of the significant, interesting strengthening of the  government administration. The analysis concerns the times before the 2015, when the dramatic crisis really begun, showing the early signs of it  and the growing gap between legislation and the real role of the parliament and local government in  the time of the information revolution. It helps us to understand the current situation in the whole complexity but doesn’t mean the resignation of the fundamental  values ‒ as the rule of law ‒ by proposing the  changes in the understanding of the role of the  public administration in the modern state.
Keywords: division authorities; independent control bodies; public administration domain; executive power; public administration